The Effect of Sharia Transactions and Business Ethics Commitment on the Sustainability of MSMEs with Financial Accountability as an Intervening Variable (A Study of MSMEs in Medan Marelan District) - Mahyudin, Mahyudin; Muda, Iskandar; Soemitra, Andri; Yusrizal, Yusrizal (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the effect of implementing sharia transactions and business ethics commitment on the sustainability of Micro, Small, and Medium Enterprises (MSMEs), with financial accountability as an intervening variable, in MSMEs in Medan Marelan District. A quantitative approach was used through the Structural Equation Modeling–Partial Least Square (SEM-PLS) method with 327 respondents. The results of the study indicate that, directly, the implementation of sharia transactions and business ethics commitment have a significant effect on the sustainability of MSMEs. However, the implementation of sharia transactions has a negative effect on financial accountability, while business ethics commitment has a positive effect on financial accountability. Financial accountability itself was found to have a positive and significant impact on the sustainability of SMEs. Indirectly, business ethics commitment enhances SME sustainability through financial accountability, while the implementation of sharia transactions reduces SME sustainability through the financial accountability channel. These results highlight the importance of synergizing sharia values with accountable financial administration practices to achieve business sustainability. This study contributes theoretically to the development of a sharia-based SME business model, while also providing practical recommendations for business actors and stakeholders to strengthen accounting education and business ethics in SME operations.